Evaluation of a Sustainable Concrete Design with Fly Ash Type C and Expanded Clay to Improve Workability and Ensure Efficient Performance - López, Valery (2025)
The construction industry is key to economic development, with cement as an essential material, despite its high environmental impact due to CO2 emissions. Despite the relevance of concrete, it faces challenges such as the loss of workability that leads to inadequate practices affecting its strength and durability. This research proposes a modified concrete mix design with 20%, 40% and 50% of fly ash type C as a replacement of Portland cement and 5% of expanded clay as a substitute for coarse aggregate to improve the workability of fresh concrete and guarantee the rest of its properties for its reliable use in construction. The characterization of materials, the design and preparation of concrete mixes and the evaluation of the physical and mechanical properties of concrete are contemplated. The results showed that with replacements of up to 20% fly ash and 5% expanded clay, the slump of fresh concrete can be increased by 50% compared to a conventional mix. Also, with this replacement rate, the concrete achieved a 28-day compressive strength at only 4.02% of its design value.